1973
DOI: 10.1029/wr009i001p00118
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of heat exchange at the air‐water interface

Abstract: The basic exchange equations for air-water interface are approximated by the Taylor series expansion around an undefined base temperature in order to calculate short-term heat exchanges. The expression 'short-term' is used here to indicate averaging over a period on the order of 1 hour. Numerical tests based on data from two shallow streams verify that the base temperature should be chosen so as to minimize deviations between the base temperature and the actual water temperature. The daily average natural temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Short-circuiting can be enhanced by station- Adams [1982]. This is a reasonable approximation except when the water temperature deviates substantially from the equilibrium temperature [Yotsukura et al, 1973], as occurs when the timescale of variation for Toe is short compared to theat , for example, over synoptic and diurnal timescales.…”
mentioning
confidence: 96%
“…Short-circuiting can be enhanced by station- Adams [1982]. This is a reasonable approximation except when the water temperature deviates substantially from the equilibrium temperature [Yotsukura et al, 1973], as occurs when the timescale of variation for Toe is short compared to theat , for example, over synoptic and diurnal timescales.…”
mentioning
confidence: 96%
“…Low flows can also place stress on invertebrates as a result of increases in temperature (Yotsukura et al 1973;Jobson 1977), and it is possible that some of the observed changes in invertebrate communities were a result of high temperatures. For example, Quinn et al (1994) found that taxa such as Deleatidium had a relatively low tolerance to warm waters, with over 50% of test organisms perishing at a 96-h exposure to temperatures >22.6°C.…”
Section: Interactions With Periphyton and Flowmentioning
confidence: 99%
“…correspond with recorded data more closely when computed values of equilibrium temperature are used. The assertion by Yotsukura, et al (1973) that "the short-term equilibrium temperature has no merit as a base ternperature of linearization" has been proven correct in this case. Since calculated equilibrium temperature performed poorly in modeling water temperature, no attempt was made to establish a relation between air and equilibrium temperatures.…”
Section: 13mentioning
confidence: 91%
“…Jobson's simplified model requires a minimum of meteorological data, using only equilibrium temperature and windspeed. According to Jobson (1980a, p. 27 (Edinger and Geyer, 1965;Dingman et al, 1968;Jobson, 1973;Paily et al, 1974;Hills and Viskanta, 1976;Jackman and Yotsukura, 1977) Other authors investigated the theoretical aspects of water temperature modeling (Edinger et al, 1968;Edinger, 1970;Dingman, 1972;Yotsukura et al, 1973;and Noble, 1981) as well as practical applications (Brown, 1969;Morse, 1970Morse, , 1972Brocard and Harleman, 1976;Jobson, 1980aJobson, , 1980bStang, 1982;Laenen and Hansen, 1985).…”
mentioning
confidence: 99%